Pteridoflora del estado de Morelos, México. Lista de familias, géneros y especies - Riba, Ramon; Pacheco, Leticia; Valdes, Arturo; Sandoval, Yolotzin (Instituto de Ecología, A.C., 1996)
For the state of Morelos 158 species and 15 varieties of pteridophytes, distributed in 50 genera and 21 families are recorded. The distribution of the taxa in the municipalities of the state is given. The genera most diversified are Cheilanthes (18 spp.), Asplenium (13 spp.) and Polypodium (12 spp.) The municipalities with more species are Cuernavaca (92 spp.), Tepoztlán (72 spp.) and Huitzilac (71 spp.).